2022
DOI: 10.1161/cir.0000000000001095
|View full text |Cite|
|
Sign up to set email alerts
|

2022 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations: Summary From the Basic Life Support; Advanced Life Support; Pediatric Life Support; Neonatal Life Support; Education, Implementation, and Teams; and First Aid Task Forces

Abstract: This is the sixth annual summary of the International Liaison Committee on Resuscitation International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. This summary addresses the most recently published resuscitation evidence reviewed by International Liaison Committee on Resuscitation Task Force science experts. Topics covered by systematic reviews include cardiopulmonary resuscitation during transport; approach to resuscitation after drownin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 397 publications
(842 reference statements)
0
20
0
Order By: Relevance
“…Thus, this study does not support the need to modify current recommendations by reintroducing vasopressin as an alternative drug for CPR. However, there are other studies that have shown benefits from a combination of vasopressin with corticosteroids for IHCA on a short-term outcome, but with more uncertainty regarding survival and neurological recovery [ 23 , 24 , 25 ].…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…Thus, this study does not support the need to modify current recommendations by reintroducing vasopressin as an alternative drug for CPR. However, there are other studies that have shown benefits from a combination of vasopressin with corticosteroids for IHCA on a short-term outcome, but with more uncertainty regarding survival and neurological recovery [ 23 , 24 , 25 ].…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…During cardiac arrest, CBF is already losing 60% during chest compression only, and it needs at least 3 min of ROSC to be normalized[ 48 ]. The current Western guidelines do not recommend using Vasopressin and glucocorticoids in IHCA and OHCA[ 45 , 49 ]. However, few studies attributed the improvement of PAMD and peri-arrest cerebral ischemia to the impact of Vasopressin on the early improved post-arrest mean arterial pressure and central venous oxygen saturation, the use of less dosages of epinephrine, the shorter duration of CPR, and the use of methylprednisolone during resuscitation[ 36 , 44 , 50 ].…”
Section: Hemodynamic Status and Pamdmentioning
confidence: 99%
“…Nevertheless, after rewarming, a more extended period of vasopressor support is still needed in patients with OHCA[ 77 ]. The 2022 International Consensus on Cardiopulmonary Resuscitation recommended not to routinely use pre-hospital cooling with a rapid infusion of large volumes of cold intravenous fluid immediately after ROSC and suggested active fever prevention for at least 72 h for patients who remain comatose after ROSC[ 49 ]. Also, patients who remained in a coma and had mild hypothermia after ROSC should not be actively rewarmed to attain normal body temperature[ 49 ].…”
Section: Multi-disciplinary Approach For Pamd and Circulatory Failurementioning
confidence: 99%
“…They recommend, either implicitly or explicitly, its use during CPR. However, many guidelines by major national and international resuscitation societies are either equivocal or warn against the general use of ultrasound in ALS [ 7 , 8 , 9 , 10 ]. These guidelines cite lack of evidence of effectiveness and potential harm from performing ultrasound during ALS resuscitation.…”
Section: Introductionmentioning
confidence: 99%